Utveckling av en äldre villaträdgård : från oplanerad till planerad - Petersson, Anders (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2007)
The result of this work is a plan for the development of an 1128 m2 elderly raised garden. The purpose has been to create an overall plan covering the long-term development of the garden.